Perilaku Peserta Didik Attention Deficit and Hyperactivity Disorder (ADHD) dalam Pembelajaran - Mansyur, Madaliyah Izah; Handayani, Arri; Rakhmawati, Dini (Tematik: Jurnal Penelitian Pendidikan Dasar, 2024)
Learning is an interaction process involving students, educators, and learning resources within a learning environment. However, today's elementary school students exhibit diverse behaviors, such as restlessness, difficulty in following instructions, and lack of focus, which can indicate emotional and behavioral disorders like Attention Deficit Hyperactivity Disorder (ADHD). Understanding ADHD symptoms and contributing factors is crucial for educators to minimize associated problems and provide appropriate interventions. This paper aims to describe the behaviors of students with ADHD in learning contexts. Utilizing a literature study method, data were sourced from relevant books and journals. The findings reveal that students with ADHD display inattentive behavior (difficulty paying attention), hyperactive behavior (inability to stay still), and impulsive behavior (acting without thinking). These behaviors significantly impact the learning process, underscoring the need for tailored educational strategies to support ADHD students.